Biodiesel synthesis from Calophyllum inophyllum oil with different supercritical fluids. (October 2017) - Lamba, Neha; Gupta, Kaveri; Modak, Jayant M.; Madras, Giridhar
Graphical abstract: Highlights: FAMEs were synthesized from surahonne oil using four different supercritical fluids. Kinetic study for all the reactions was performed by varying time and temperature. Rate constants and activation energies of the reactions were obtained and discussed. Abstract: Biodiesel or fatty acid methyl esters (FAMEs) is primarily synthesized using edible vegetable oils and methanol with a catalyst. However, in the present study, FAMEs were synthesized from a non-edible oil ( Calophyllum inophyllum also called as sura honne, Punnagam, Alexandrian Laurel) in different supercritical fluids: methanol (MeOH), methyl tert-butyl ether (MTBE), methyl acetate (MeOAc) and dimethyl carbonate (DMC) non-catalytically. Reactions were performed from 523 K to 673 K at 30 MPa with a molar ratio of 40:1 with times varying from 3 min to 3 h. Conversions higher than 80% were obtained within 30 min for oil reaction with MeOH and DMC at 623 K and conversions of 60% and 70% were obtained at 673 K with MeOAc and MTBE, respectively. Pseudo first order kinetics was used to obtain the rate constants and the activation energies followed the order: EMeOH  <  EDMC  <  EMeOAc  <  EMTBE .